Factores de riesgo asociados a gastrosquisis en neonatos hospitalizados en el Hospital Regional de Loreto 2024 – 2025 - Nuñez Marroquin, Lelly Lileth (2025)
This project aims to identify and analyze the risk factors associated with gastroschisis. The objective is to explore the incidence of gastroschisis in preterm neonates admitted to the neonatology service of the hospital during the period from 2024 to 2025. The study is observational, case-control, prospective, and cross-sectional, using a sample of 28 patients admitted to the neonatology service. The SPSS version 26.0 program will be used for statistical analyses. In the descriptive analysis, statistical values will be presented through frequencies and percentages for qualitative variables, as well as the mean and standard deviation for quantitative variables. Regarding the inferential analysis, Fisher's Exact Test will be used, which will allow the assessment of the association between two dichotomous variables when the study sample size is small and the necessary conditions for the application of the test are not met. In all analyses, a P value <0.05 will be considered statistically significant.